Sitting Position and Low Back Pain (LBP) Incidents in Online Learning During the Pandemic of Covid-19: A Correlational Study - Angga Wilandika; Zainab Zakiyah Zahrotul Firdaus; Rahmat (Journal of Nursing Science Update (JNSU), 2022)
COVID-19 has an impact on the education sector. Transitioning from face-to-face to online learning puts students at risk for back pain as they must perform most tasks in a sitting position with a non-ergonomic posture. The aim was to analyze the relationship between the sitting position and low back pain during online learning. In this study, we used a cross-section design. A total of 224 nursing students participated in the study. Sampling was done randomly, and data collection using online questionnaires. Data analysis was done descriptively and inferentially. The Chi-Square test was used to determine the correlation between sitting position and low back pain. The results showed that almost half (49.1%) of students sat down when learning online, and the incidence of low back pain in students was as much as 45.1%. In addition, the results also showed no significant association (p-value = 7,035 ≥ 0.05; r = 0.030) between sitting position and low back pain incidence in nursing students during online learning during the COVID-19 pandemic. The sitting position factor is not the primary determinant of low back pain. Therefore, further research is needed concerning other low back pain events.